2017
DOI: 10.1038/s41598-017-09894-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic analogs of an Entamoeba histolytica glycolipid designed to combat intracellular Leishmania infection

Abstract: Intracellular pathogens belonging to the genus Leishmania have developed effective strategies that enable them to survive within host immune cells. Immunostimulatory compounds that counteract such immunological escape mechanisms represent promising treatment options for diseases. Here, we demonstrate that a lipopeptidephosphoglycan (LPPG) isolated from the membrane of a protozoan parasite, Entamoeba histolytica (Eh), shows considerable immunostimulatory effects targeted against Leishmania (L.) major, a represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 39 publications
(57 reference statements)
1
20
0
Order By: Relevance
“…We therefore examined the hemolytic activity and cytotoxicity of the synthetic compounds in vitro. Consistent with earlier results (20), ␣-GalCer and EhLPPG were weakly hemolytic, while the synthetic analogs showed minimal hemolytic activity and negligible cytotoxicity against human peripheral blood lymphocytes or murine splenocytes (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We therefore examined the hemolytic activity and cytotoxicity of the synthetic compounds in vitro. Consistent with earlier results (20), ␣-GalCer and EhLPPG were weakly hemolytic, while the synthetic analogs showed minimal hemolytic activity and negligible cytotoxicity against human peripheral blood lymphocytes or murine splenocytes (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
“…In vitro activities of synthetic EhPIb analogs against L. major infection. We previously reported that EhLPPG and the first set of synthetic EhPI analogs reduced parasite loads in L. major-infected macrophages (20). Here, we tested the antileishmanial activity of the newly synthesized compounds Eh-1, Eh-2, Eh-3, Eh-4, Eh-5, and Eh-6 against L. major-infected bone marrow-derived macrophages (BMDMs) and human THP1 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations